Association of The Mthfr C677t, Factor V (Leiden) G1961a and Prothrombin G20210a Gene Mutations with Recurrent Spontaneous Aboration (Rsa) in Duhok Province - Mohammed, Shaima S.; Al-Timimy, Rana A.; Hassan, jinan N.; Mahmood, Najat T. (Science Journal of University of Zakho, 2018)
Genetic causes of thrombophilia have been suggested as a possible cause of recurrent pregnancy loss (RPL). Fifty female patients aged between 21- 40 years and experienced at least two times early pregnancy loss were enrolled in the current study. Blood samples were aspirated, infectious (TORCH), hormonal (gonadotrophines, steroids, and thyroid hormones), ultrasonic, and serological (anti-lupus and anti-phospholipid antibodies) evaluations were conducted to exclude any individual candidate who had been suspected to have causes of early pregnancy loss rather than the genetic attribute. DNA from each particular sample was extracted by components of (FVL-PTH and MTHFR)StripAssay®A kit Vienna Lab Diagnostics GmbH, Vienna, Austria).this kit includes three steps: (1) DNA isolation, (2) Multiplex PCR amplification was performed by using biotinylated primers, for detecting different mutations in the three genes of interest (FVL-PTH and MTHFR) (3) Hybridization of amplification products to a test strip containing allele-specific oligonucleotide probes immobilized as an array of parallel lines. The results revealed that 24 samples out of 50 had MTHFR C677T mutations while 2 samples only had FV (G1691A)mutation while prothrombin mutation (G20210A)has not been detected. In conclusion: genetic mutation had significant impact in patients suffered recurrent pregnancy loss.